The Empowering Eco-Cultural Entrepreneurship for Sustainable Livelihoods of Ditch Garden Community Along the Bang Pakong River in Chachoengsao Province - Sophonsuwapap, Paiboon (Area Based Development Research Journal, 2023)
The community along the Bang Pakong River, located in Ban Khlong Bang Kluai and Ban Khlong Lat, Khlong Chuk Krache sub-district, Muang district, Chachoengsao province of Thailand, relies on middlemen for agricultural product sales. However, the COVID-19 pandemic disrupted production and caused financial hardships for the farmers. In response, the community sought to harness the resources of ditch garden by developing eco-cultural entrepreneurship. This study employed the 8-step indicator concept of eco-cultural entrepreneurs and the principles of the local economy. The community’s approach involved: 1) promoting eco-cultural values; 2) raising awareness about the potential of ditch garden community and identifying the needs of eco-cultural entrepreneurs through cultural mapping; 3) developing the skills of eco-cultural entrepreneurs to create innovative eco-cultural products; 4) fostering entrepreneurship to ensure the sustainability of both the products and the community; 5) synthesizing knowledge through reflective learning and internal changes among eco-cultural entrepreneurs; and 6) sharing community stories and lessons learned to benefit the wider community. The outcomes include the emergence of 13 eco-cultural entrepreneurs who possess a deep understanding of local resources, as well as the development of eight ecological products, such as processed bananas, cultural learning classrooms, community learning paths, and a local knowledge set. These initiatives have provided alternative livelihood opportunities for eco-cultural entrepreneurs and community members. For instance, members of the Ban Khlong Bang Kluai banana processing group now earn an average monthly income of 111 USD per person. Additionally, the ditch garden community has generated income by leveraging eco-services and ensuring equitable distribution of tangible benefits. This case study highlights the potential of eco-cultural entrepreneurship as a sustainable approach for community development and economic resilience.